Kinematics and Electromyographic Analysis of Gait with Different Footwear - Kelencz, Carlos Alberto; Muñoz, Ingrid Solange Sepúlveda; Oliveira, Paulo Rui de; Mazziotti, Bruno; Amorim, Cesar Ferreira (Archives of Pharmacy and Pharmaceutical Sciences, 2017)
Kinematic analysis and surface electromyography are tools being used as important methods to evaluate the human gait and to analyze different types of footwear aiming modifications and adaptations to the human locomotor system, especially of the feet. The aim of the present study was to analyze through electromyography (EMG) the muscles tibialis anterior (TA) and gastrocnemius lateralis (GL) and gastrocnemius medialis (GM) and to capture digital images of the human gait in four different footware situations, barefoot with tennis, platform shoes and high heels. Twenty healthy women with a mean age of 22.6 years took part in this experiment, which was performed on a treadmill at a speed of 3.8 m/s. The results showed that shoes that do not allow a normal movement of the tarsal bones caused changes in the trajectory of the gait, which promotes a greater muscular movement. This study concluded that shoes closer to a normal position and allow greater mobility of the feet, decrease muscular demands, which in everyday situations cause less localized muscular fatigue.